STUDENT SATISFACTION IN USING THE APPLICATION OF NON-CASH TRANSACTIONS - Intan Indah Eka Fitri; Isnaniah Muslim; Nadila Rahayu Putri; Zul Azmi (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2022)
This study aims to determine the level of student satisfaction in the use of non-cash payment applications. This study aims to determine the level of student satisfaction in the use of non-cash payment applications. This type of research used a qualitative approach, by conducting interviews and observations as data collection techniques. In addition, the author also uses a literature study by reading some of the literature that supports the problems studied through previous journals to strengthen the data in the study. The results of research on students of the Faculty of Economics and Business, Universitas Muhammadiyah Riau stated that they rarely use non-cash payment applications. It is known that some students often use cash or cash payments. One of the reasons is because students get pocket money from their parents in cash so students use it for their payment activities